Internal Brace Ligament Augmentation versus Anatomical Repair with Hamstrings of the ACL – A Clinical Data Comparison Study - Todhe, Dritan; Çipi, Rezart; Hysenaj, Alban (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: Investigation into the clinical results of internal brace ligament augmentation technique compared to the simple anatomical repair of the anterior cruciate ligament (ACL). METHODS: From May 2016 to November 2019, 128 patients underwent an operation using the internal brace technique. During the same time, 104 patients were operated on using the simple anatomical ACL repair. The mean age was 22.5-year-old for the first group and 26.8-year- old for the second one. The minimum follow-up was 24 months. All the patients performed an X-ray and magnetic resonance imaging. Two hypotheses were raised to assess the superiority of the internal brace technique versus the anatomical one in the early post-operative phase and the rehabilitation one. RESULTS: The mean operation time was 71 (65–75) min for the internal brace (IB) and 62 (55–65) for the anatomical. We had two post-operative infected knees in the first group (IB) and no infection in the second one. The clinical stability test results were much better in the IB group using the KT 1000. The rehabilitation phase showed a superior IB technique. The return to sport-time of the sportsmen was 6 months for the first group and 7–8 months for the anatomical. All the IB-operated patients found physiotherapy significantly easier than the anatomical ones. CONCLUSIONS: IB-technique performs better clinical outcomes than the anatomical repair. The presence of a foreign body (Ultrabraid) inside the knee may be a risk factor contributing toward the elevated infection rate. The IB technique costs are significantly more expensive compared to the anatomical but the low physiotherapy costs compensate for the final result.